Let f ( x ) be a differentiable function satisfying f ( y ) − f ( x ) = y y x x f ( x x y y ) for all x , y ∈ R + . It is given that f ′ ( 1 ) = 1 . Find the value of ∣ ∣ f ( e ) f ( e 1 ) ∣ ∣
Notation: e ≈ 2 . 7 1 8 is the Euler's number .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
booster test zindabad
Can you clean up the third/fourth line? You seem to have already assumed that x = 1 , but haven't replaced that in the firmula.
Log in to reply
@Rishi Sharma Esp with the report, I've edited the functional equation. Can you review through your solution again, and see why the error occured?
Problem Loading...
Note Loading...
Set Loading...
First by simple inspection we can see that f ( 1 ) = 0 . Now as the function is differentiable h → 0 lim h f ( x + h ) − f ( x ) = f ′ ( x ) we can replace y by x + h and x by x in the above differential equation to get. h → 0 lim h ( x + h ) ( x + h ) x x f ( x x ( x + h ) x + h ) = f ′ ( x ) Now lim h → 0 ( x + h ) ( x + h ) x x = 1 . Also using f ( 1 ) = 0 we get. h → 0 lim h f ( x x ( x + h ) x + h ) − f ( 1 ) = f ′ ( x ) Now note that h → 0 lim x x ( x + h ) x + h − 1 f ( x x ( x + h ) x + h ) − f ( 1 ) = f ′ ( 1 ) = 1 . Substituting it back we get h → 0 lim h ( x x ( x + h ) x + h ) − ( 1 ) = f ′ ( x ) After using L'hopital's rule we get f ′ ( x ) = ln x + 1 Solving the differential equation and using at x=1 y=0. we get f ( x ) = x ln x So f ( e ) = e and f ( e 1 ) = e − 1 .So the answer is 1